Biodegradability enhancement of landfill leachate nanofiltration concentrate using sequential and combined electrochemical processes - Yucel, Esra; Ozen, Irem; Cene, Gulay Arslan; Ilhan, Hilal; Guvenc, Senem Yazici; Can-Guven, Emine; Varank, Gamze; Demir, Ahmet (ELSEVIER, 2025)
In this study, the treatment of landfill leachate nanofiltration concentrate (LNFC) was investigated using sequential (two distinct stages, one following the other) and combined (two mechanisms operating simultaneously in a single reactor) electrochemical processes. In the first stage, initial pH, applied current, and reaction time were optimized for individual processes: electro-oxidation (EO), peroxi-coagulation (PC), and electrochemical-peroxidation (EP). In the second stage, sequential (EO-PC, PC-EO, EO-EP, EP-EO) and combined (EO/PC, EO/EP) processes were applied with the optimal conditions determined in the first stage. Under optimum conditions (pH 5; applied current 1 A; reaction time 60 min), chemical oxygen demand (COD) removal efficiencies of 38.9 %, 42.1 %, and 53.1 % were obtained for the EO, PC, and EP processes, respectively. Enhanced COD removal was obtained by sequential processes, yielding removal rates of 65.6 % for EO-PC, 71.1 % for PC-EO, 78.3 % for EO-EP, and 83.6 % for EP-EO. The highest efficiencies were observed in the combined systems, with COD removals of 76.4 % for EO/PC and 89.1 % for EO/EP. The lowest specific energy consumption (SEC) was calculated as 31.2 kWh/kg COD for EP among the single processes, 41.0 kWh/kg COD for EP-EO among the sequential processes, and 47.5 kWh/kg COD for EO/EP among the combined processes. These findings suggest that EP-based systems require less energy than EO-based systems. The EO/EP process can be proposed as an alternative treatment for LNFC due to its compliance with the discharge standards (500 mg/L for COD for leachate) specified in the Water Pollution Control Regulation of T & uuml;rkiye and its relatively low SEC.
Keywords: Advanced oxidation; Electrochemical treatment; Landfill leachate; Specific energy consumption; Wastewater treatment; ADVANCED OXIDATION PROCESSES; ELECTRO-FENTON PROCESS; WASTE-WATER; ELECTROCOAGULATION PROCESS; ELECTROOXIDATION; DEGRADATION; REMOVAL; REMEDIATION; EFFLUENT; INDUSTRY; Engineering; Water Resources